Innovative Management and Economic Analysis of Business Models in Sports Enterprises: Enhancing Competitiveness Through Strategic Practices - Xiaoyu Li (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
This study delves into the correlation between economic outcomes and the competitiveness of innovative management practices and sports organisations. In today's rapidly evolving sports industry, it is crucial to recognise the importance of innovation in reaching organisational objectives. As new opportunities and challenges arise in the digital and data-driven landscape, staying ahead of the curve is essential. This study utilises empirical and quantitative economic analyses, as well as insights from industry experts and practitioners, to investigate the adoption patterns of innovative practices and their effects on different performance indicators. The financial statements of major European football clubs were examined in this study to showcase the feasibility and future prospects of organisations that prioritise innovation in response to the COVID-19 crisis. The research primarily concentrates on the influence of innovations like smart stadiums and digital strategies on market capitalisation and revenues, achieved through enhanced fan engagement. The findings indicate that incorporating innovative approaches to resource management can have a positive impact on economic performance. In addition, the investigation uncovers a clear link between the adoption of innovative strategies and improved performance in sports and finances, establishing a mutually beneficial cycle. Nevertheless, this study highlights concerns regarding employee turnover and job satisfaction, underscoring the importance of incorporating personnel culture and well-being into a company's innovation system. Important factors to consider involve ensuring that strategic innovation is aligned with business objectives, consistently investing in digital assets and data insights, and making infrastructure advancements to create new avenues for profitability. This study further highlights the significance of fostering innovation in organisational processes as a means of preparing for future crises. This study provides valuable insights to the literature on sports management innovation and offers practical implications for industry practitioners. It is evident that the successful adoption of cutting-edge management strategies will play a vital role in maintaining a competitive edge as the sports industry continues to develop.